2013
DOI: 10.1007/s00374-013-0883-6
|View full text |Cite
|
Sign up to set email alerts
|

Relating microfeatures of soil organic matter to C stabilisation: optical microscopy, SEM-EDS, abiotic oxidation

Abstract: 1We investigated the relationships between microscale distribution of soil organic matter 2 (SOM) features and their stability by combining optical microscopy, SEM-EDS analysis and 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Consequently, we expected that OM quality, evaluated as relative C and N contents, was important in driving the proportion of OCrec and OClab. In fact, the C/N ratio is often taken as index of OM quality and was found to be related to the sensitivity to oxidation treatments (Falsone et al, 2014). In spite of this, our results showed that the relationships between CUT/N ratios and the proportions of OClab (n=79, r=-0.305, P<0.01) and OCrec (n=79, r=0.366, P<0.01) were rather poor, as the determination coefficients explained only 9 and 13% of sample variability, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we expected that OM quality, evaluated as relative C and N contents, was important in driving the proportion of OCrec and OClab. In fact, the C/N ratio is often taken as index of OM quality and was found to be related to the sensitivity to oxidation treatments (Falsone et al, 2014). In spite of this, our results showed that the relationships between CUT/N ratios and the proportions of OClab (n=79, r=-0.305, P<0.01) and OCrec (n=79, r=0.366, P<0.01) were rather poor, as the determination coefficients explained only 9 and 13% of sample variability, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaics created with sequential images taken from a microscope were proposed as a solution to the spatial resolution and to increase the area of the soil thin section studied; however, they were constructed from a small area only of the thin section (Adderley et al, 2002;Falsone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To measure pores, multiple images of the same representative aggregates were taken under both plane (PPL; Figure S1-a) and crossed polarized light (XPL) at 0.5 and 15° (Falsone et al, 2014). This was necessary to distinguish between pores and quartz, since both were translucent under PPL.…”
Section: Total Porosity and Pore Size Distributionmentioning
confidence: 99%
“…In this work we took into account the Al:C, Fe:C and Ca:C molar ratios as indicators of the degree of organicmetals/minerals interactions (Falsone et al, 2014).…”
Section: Sem-eds Analysis On the Aggregate Thin Sectionsmentioning
confidence: 99%